On the Molecular Modeling Analyses of Novel HIV-1 Protease Inhibitors Based on Modified Chitosan Dimer. (19th March 2015) - Al-Fifi, Zarrag; Saleh, Noha A.; Elhaes, Hanan; Ibrahim, Medhat
Abstract : The molecular modeling studies include quantitative structure activity relationship, IR spectra, and docking calculations, occurring for novel inhibitors based on chitosan dimer which were tried as HIV protease. The inhibitors were investigated with molecular modeling calculations at different level of theories. Each compound has phenol with hydroxymethylcarbonyl (HMC) group which added to chitosan in positions 2, 3, 2′, or 3′. The geometry of studied compounds is optimized with semiempirical PM3 method. Quantitative structure activity relationship (QSAR) properties of the suggested compounds are calculated at the same level of theory. Depending on QSAR calculations, the compounds with positions 2 and 2′ are less hydrophilic. The position 2′ compound makes good docking interaction into HIV protease active site. Calculated IR spectra indicate that the interaction through hydrogen bonding through the hydrogen of OH at positions 3 and 3′ gives rise to two OH bands one for chitosan and the other for phenol and HMC group. While at position 3′ CH band starts to appear.